2022
DOI: 10.3389/fenvs.2022.818134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Broadband Infrastructure on Rural Household CO2 Emissions in China: A Quasi-Natural Experiment of a “Broadband Village”

Abstract: This paper explores how broadband infrastructure affects rural household carbon dioxide emissions (HCE). Based on the Environmental Kuznets curve hypothesis, a quasi-natural experiment of a “Broadband Village” (B&V) in China is conducted. Panel data from 9,790 rural households were collected as part of the China Family Finance Survey (CHFS). The consumer lifestyle approach was used to calculate HCE and a Difference-in-Differences (DID) model was used to analyze the impact of a B and V pilot project on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 89 publications
2
6
0
Order By: Relevance
“…The above three core issues for research and progress have important theoretical value and policy implications for analyzing the impact of ICTs on ACRE. Indeed, broadband is the main infrastructure for carrying information, and household broadband penetration within a region is often used to represent ICTs development level [36][37][38]. Our paper defines broadband adoption as an ICTs application.…”
Section: Introductionmentioning
confidence: 99%
“…The above three core issues for research and progress have important theoretical value and policy implications for analyzing the impact of ICTs on ACRE. Indeed, broadband is the main infrastructure for carrying information, and household broadband penetration within a region is often used to represent ICTs development level [36][37][38]. Our paper defines broadband adoption as an ICTs application.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed and Le (2021) used the data from the six ASEAN countries from 1990 to 2018 and found that broadband development is conducive to reducing carbon emissions. At the same time, researchers also found this fact in North America, China, South Asia, and other countries and regions Usman et al, 2021;Rao et al, 2022b). Further, from a spatial perspective, network infrastructure significantly promotes local carbon emission reduction efficiency and positively affects neighboring regions (Wu et al, 2021b).…”
Section: Introductionmentioning
confidence: 81%
“…The key assumption for using the DID method is that the experimental and control groups exhibit parallel trends [37], meaning that, before the implementation of the "Broadband China" strategy, the carbon emissions of listed companies in both groups had a relatively stable trend. In this study, following the approach of Li et al [38], we employ the Event Study Approach to investigate the dynamic effects of the "Broadband China" pilot.…”
Section: Robustness Test (1) Dynamic Effects and Placebo Testsmentioning
confidence: 99%